DIAGNÓSTICO DE CARCINOMA UROTELIAL DURANTE ESTUDIO DE BACTEREMIA POR STREPTOCOCCUS GORDONII - Ivan Vargas-Matos (Asociación Colombiana de Infectología, 2021)
Streptococcus gordonii bacteremia is rare. Its isolation in blood culture translates into high clinical significance and the diagnostic approach should be directed towards the search for underlying entities such as hematologic malignancies, valvular heart disease, pneumonia, structural changes of the head and neck, immunosuppression and other related conditions. No reports have been identified in patients with urinary tract neoplasia as a possible condition of bacteremia by this agent. The case of a patient who was diagnosed with high-grade urothelial carcinoma during the study of bacteremia by this microorganism is described.